(Endogenous) growth slowdowns - Miguel A. León-Ledesma; Katsuyuki Shibayama (University of Kent, School of Economics, 2023)
We develop a model where temporary non-technology shocks can lead to permanent changes in the rate of growth of total factor productivity (TFP). The key ingredient of the model is a matching processes between basic researchers, product developers, and the stock of knowledge of the economy. In this context, search externalities generate vicious and virtuous cycles in R&D. The model has a unique equilibrium path but multiple balanced growth paths (BGPs) with different growth rates. After a deep or long-lived shock, the economy can transit between these BGPs, generating "super-hysteresis" in TFP. We calibrate the model in the context of the Japanese growth slowdown and show that, quantitatively, it can explain well the TFP growth decline after the financial crisis in the 1990s. The simultaneous occurrence of demographic shocks and a persistent but temporary financial crisis gave rise to a "wretched coincidence" resulting in the growth slowdown.
Keywords: O40; O49; E32; 330; Growth slowdowns; permanent effects of recessions; research and development; super-hysteresis